Animal acceptance and preference of legumes (Arachis pintoi, Stylosanthes guianensis and Centrocema macrocarpum) in the tropics - Romero Delgado, Gelver (2022)
The value of a forage plant depends not only on its productivity but also on its acceptance and preference of the animals. The aim of this study was to evaluate the forage yield, chemical composition, acceptance and preference of three forage legumes (Arachis pintoi, Stylosanthes guianensis and Centrocema macrocarpum) in Girolando female calves under tropical conditions. Experiment 1: Production (KgMS/h) and Nutritional Value (%) of the species from quarterly cuts and for one year after the growth phase has ended. Experiment 2: Acceptability was determined by the intake rate (g/min) of each species in six calves without experience in their consumption, when they were offered individually to the animals for 5 min daily for three consecutive days. Experiment 3: Preference was estimated from the relative intake (%) in individual pens when the three species were offered for 10 min daily for five consecutive days in individual pens and separated from each other by visual barriers to avoid interactions between animals. Yield and nutritional value varied significantly between species (p<0.001): 6019, 4057 and 1236 kg/DM/ha, crude protein 14.45, 16.32 and 16.98% and NDF 58.63, 57.51 and 50.79% in S. guianensis, C. macrocarpum and A. pintoi, respectively, while the acceptance and preference tests revealed that A. pintoi (8.18 gMS/min and 45.97%) and S. guianensis (8.14 gMS/min and 33.31%) showed greater acceptance and preference with relation to C. macrocarpum (4.52 gMS/min and 20.72%). Consequently, A. pintoi and S. guianensis provide an opportunity to supply animals with nitrogen in less time when they are supplemented in protein banks.